Gestión y Desarrollo Turístico en el Cantón Salcedo, Provincia de Cotopaxi. - Tonato Chiluisa, Jessica Marisol (2023)
The Salcedo canton is a tourist place that offers various activities to its visitors since it has beautiful landscapes and countless natural and cultural tourist resources. The research aims to determine if there is a relationship between management and tourism development in the Salcedo canton, Cotopaxi province. The methodology that was used in this work is the following: the type of research is documentary and field, the technique used is the observation in which notes were made that help the investigation and then, with the information, carry out surveys for the independent and dependent variables. Next, the surveys were applied and then the IBM SPSS Statistics 21 program was used to tabulate the information from the applied surveys and obtain the results which gave more significant importance in planning, organization, direction, control, improvement of the facilities, suitable services and job creation, in addition, it was determined that management plays a fundamental role for tourism development in the Salcedo canton, Cotopaxi province. Next, the general and specific hypotheses were confirmed with the Rho Spearman test. Finally, with the information collected, the proposal was carried out whose theme is Management Strategies to promote Tourism development in the canton of Salcedo, Province of Cotopaxi, in which a SWOT analysis was carried out, strategies were determined and management indicators were identified. (Planning, organization, direction, and control).